Analisis Penyebab Kesulitan Belajar Siswa pada Mata Pelajaran Sejarah Kebudayaan Islam di Madrasah Tsanawiyah Swasta Muhammadiyah 2 Banjarmasin - Sinta Masitha; Nuril Huda (CV. ITTC INDONESIA, 2025)
Islamic Cultural History is one of the core subjects in Islamic educational institutions. Its materials cover the origins of events, figures, places, culture, Islamic law, and the development of knowledge. This subject provides valuable lessons (ʿibrah) for students to deepen their moral and intellectual understanding. However, due to its broad and complex scope, many students experience learning difficulties during the learning process. This study aims to analyze the factors that cause students’ learning difficulties and to identify appropriate solutions in teaching Islamic Cultural History at Muhammadiyah 2 Private Madrasah Tsanawiyah (Islamic Junior High School) in Banjarmasin. The research employed field research with a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The data analysis process consisted of three stages: data reduction, data display, and conclusion drawing. The results show that learning difficulties are caused by low motivation, poor behavior, lack of preparation, drowsiness, and weak physical condition. Teachers addressed these issues by creating an enjoyable learning environment, using simple and clear language, providing remedial sessions, repeating core materials, and involving parents in behavioral guidance. These strategies are expected to increase students’ motivation, participation, and comprehension in learning Islamic Cultural History.